Advertisement Business Financial Strategy During The COVID-19 Pandemic: A Case Study of Satria Advertisement Company - Ronald Septyanto Suparta; Liliana Inggrit Wijaya (Syntax Literate, 2023)
The COVID-19 pandemic has had a major impact on the business world, including Karya Satria Advertisement companies engaged in out-of-home Advertisement. The company experienced difficulties in obtaining Financial due to strict banking policies during the pandemic and new regulations from the government during the pandemic, which also impacted the company's operations. Based on this, the purpose of this study is to explore Financial strategies that can be applied by Karya Satria Advertisement during the COVID-19 Pandemic. The approach used is qualitative and exploratory. The research data was obtained by interviewing three resource persons, consisting of the Finance Manager, Head of Magelang Branch, Head of Solo Branch. Furthermore, the data obtained were analyzed using three stages of analysis: data condensation, data presentation, and conclusions. The results showed that Karya Satria Advertisement felt the negative impact of the COVID-19 Pandemic, especially at the beginning of its spread. However, based on the company's good adaptive power and support from loyal customers, as well as strong commitment from all internal parts of the company, Karya Satria Advertisement can overcome these negative impacts. Karya Satria Advertisement has a positive response to these regulations, namely by trying their best to comply with and implement various new government regulations. The Financial strategy that can be applied by Karya Satria Advertisement is to look for alternative sources of Financial, ranging from venture capital, P2P lending, government programs, strategic partnerships, or alternative financial instruments.